Resíduos sólidos domésticos na terra indígena Rio das Cobras Ẽg tỹ nẽn vãvãm tῖ kaingag ag ga tȳ Rio das Cobras tá - Cornélio, Ilda (2017)
The Rio das Cobras Indigenous Land is the largest indigenous community in Paraná state and faces current societal challenges, including the management of household solid waste (RSD), also known as garbage. This work aimed to analyze the generation and destination of domestic waste by the indigenous families of this community. Interviews, collection and quantification of RSD were carried out with 12 families from three villages. The results show that in nine days, referring to 12 families, we collected 72.24 kg of RSD, corresponding to 0.1 kg.habitante-1dia-1 . In a second collection period, the total production was 51.68 kg, equivalent to 0.08 kg.habitante1dia-1. In addition, 91.5% of the respondents reported that they burn the garbage produced and 8.5% that the waste is thrown in the open. It was also observed that there is no understanding of the various items and categories of solid waste among the interviewees. There was some initial resistance to changes in habits by the communities in relation to the separation process and, consequently, the referral of the categorized materials to the collection of the garbage truck. With the development of the work it was noticed an improvement in the understanding of the community's role in its environment. Additionally, we emphasize the importance of environmental education actions and other public policies that minimize the impact of waste on the environment and the physical and cultural well-being of indigenous peoples. Keywords: indigenous community, environment, solid waste.